In-vitro propagation and Agrobacterium tumefaciens-mediated transformation of Jatropha curcas - Stepfanie Evert Jole (2015)
This study consisted of several parts which include development of tissue culture and regeneration system for Jatropha curcas, establishment of Agrobacteriummediated transformation system and molecular analysis to confirm the integration of transgene in plant host genome. Observation made on callus induction after 60 days of culturing. Studies showed that MS medium supplemented with 2.0mg/L NAA and 1.0 mg/L BAP with large callus (green and compact structure) resulted the highest mean fresh weight, 4.754 grams. Callus regeneration of J. curcas was carried out using MS medium supplemented with combination concentration of BAP and IBA. However, calli were unable to regenerate in any of the treatment media tested after 12 weeks of culturing. Genetic transformation protocol for J. curcas callus mediated by Agrobacterium tumefaciens was optimized using green fluorescent protein as a reporter gene. A. tumefaciens at concentration of OD600nm 0.6, showed the highest virulence on J. curcas callus. Two days of pre-culture period and 3 days of co-cultivation period were optimum for J. curcas transformations. Result also showed that 45 minutes of immersion and addition of 300 EM acetosyringone gave the highest percentage of positive transformants for J. curcas callus. The putative transformants were selected in the presence of hygromycin as a selection agent. Callus was also subjected to GUS histochemical assay analysis. Selected callus was excised and inoculated onto MS media supplemented with different concentrations of BAP and NAA in the range of 0.5mg/L to 5.0mg/L for regeneration. Molecular analyses were carried out to further confirm the expression of transgene in the putative transformants. PCR was carried out using the designed 35S primer and the result showed amplification of 454bp of 35S promoter region from the transformed callus. Real-time PCR was carried out to further confirm the integration of transgene and copy number of gene inserted in the putative transformants callus.